Uncovering Adolescents' Experiences of Early Marriage and Reproductive Health: A Qualitative Study at Blabak Community Health Center, Kandat District, Kediri - Sejati, Putri Eka; Sovia Walu; Lely Khuafa’ur Rosidah; Susiani Endarwati (Universitas STRADA Indonesia, 2025)
The age at first marriage carries risks for each woman's childbirth. The younger a woman's age at first marriage, the greater the risks to the safety of the mother and child. This study aimed to determine sexual and reproductive health knowledge regarding early marriage, its impacts, and sources of information about early marriage. This study used a descriptive qualitative design. The population was all adolescent girls in the Blabak Community Health Center (Puskesmas) area of Kediri Regency. The informants were two teenagers who had previously married early, eight who had never married early, two mothers with teenagers who had previously married early, eight mothers with teenagers who had never married early, and one midwife at the Blabak Community Health Center in Kediri Regency. The instrument used was interviews. The results showed that the majority of informants understood early marriage. In contrast, only three informants did not understand sexual and reproductive health, the impacts of early marriage, or had not received information about it. Individual counseling, not group counseling, was necessary because one-on-one counseling with respondents will increase their knowledge about early marriage.